IMPLEMENTATION OF THE TOP MANAGER 'S LEADERSHIP ROLE AS AN EFFORT TO INCREASE EMPLOYEES' WORK MOTIVATION IN MASLOW'S PERSPECTIVE OF THE HIERARCHY OF DEMANDS - Khaeruman Khaeruman (International Journal of Economy, Education and Entrepreneurship, 2022)
A top manager is significant in a company because leaders are the only people responsible for guiding, leading, guiding, motivating, and providing adequate supervision or supervision to their employees. Maslow argues that a person will be encouraged to work if his demands are filled in the hierarchy of needs theory. With this motivation, employees will work more decisive for optimal results. Maslow's theory of inspiration should be considered a general direction for managers. This research is qualitative research with a descriptive approach, namely research that produces analytical procedures that do not use statistical analysis. This qualitative study aims to analyze the top manager's leadership role to increase employee work motivation from Maslow's hierarchy of needs theory. According to the findings of this study, top managers' leadership role in increasing employee work motivation is very realistic, namely by providing inspiration, encouragement, and direction to subordinates and broad responsibilities and opportunities for them to make decisions or wisdom in completing their work. The leadership role of top managers to increase employee work motivation in the perspective of Maslow's hierarchy of needs theory is by fulfilling several requirements, including physiological needs, safety and security needs, social needs, esteem needs, and self-actualization needs